Leiomyosarcoma of the Vagina: An Exceedingly Rare Diagnosis - Nathan A. Keller; Heidi Godoy (Hindawi Limited, 2015)
Background. Primary leiomyosarcoma of the vagina is an exceedingly rare diagnosis. Current estimates are that this tumor could at most represent a mere 0.062% of malignant neoplasms in the female genital tract, although in actuality it is likely far less common. Case Presentation. A 70-year-old female gravida 3 para 2 with new onset palpable vaginal mass and pink vaginal discharge is diagnosed with primary leiomyosarcoma of the vagina. Chemotherapy is complicated by acute Lyme disease, and the patient requires a robotic-assisted total hysterectomy with bilateral salpingo-oophorectomy and partial vaginectomy. The patient remains without recurrence 18 months after surgery. Conclusion. Vaginal leiomyosarcoma is exceedingly rare with an aggressive course, high recurrence, and undetermined ideal treatment regimen. Its diagnosis can be delayed and its presentation varied. Information on this rare tumor type is predominantly through rare case reports with collective consensus on management lacking. The gynecologic oncologist must exercise prudence in individualizing treatment regimens for this rare yet aggressive malignancy.